Perbandingan Verba Kompon -Kiru Dan -Nuku Sebagai Penanda Aspek Perfektif Dalam Bahasa Jepang - Elizabeth Ika Hesti Aprilia Nindia Rini (Diponegoro University, 2019)
(Title: Comparison of Compounds Verbs -Kiru and -Nuku as Perfective Aspects Markers in Japanese) Compound verbs -kiru and -nuku are known as markers of perfective aspects that express the meaning of completion. This study aims to describe the similarities and differences in the meanings of compounds verbs -kiru and -nuku as markers of perfective aspects. The method used in this research is descriptive method. As a result of the study it was found that even though they stated the meaning of completion, the compound verb -kiru had a focus on the end point when the main part separated, while compound verb -nuku had a focus on the process. Besides adverb which follows the compound verb -kiru and -nuku is not the same. Compound verb -kiru followed by adverb saigo made and subete, whereas compound verb -nuku is followed by adverb akumade, tetteiteki, ikkan shite, hitosuji ni, tokoton, and dokomademo.